From Corporate Logic to Public Welfare: A Siyāsah Shar‘iyyah Framework for Understanding Indonesian State-Owned Enterprises - Fathudin; Anna Erliyana; Dian Puji N Simatupang (Universitas Islam Negeri Jakarta, 2026)
The establishment of BPI Danantara as Indonesia’s state-owned enterprise (SOE) super-holding has renewed debates over the balance between state control and market logic in managing strategic public assets. This article examines the normative foundations of SOE governance through the framework of siyāsah shar’iyyah, using a normative-conceptual approach grounded in classical and contemporary fiqh literature and constitutional analysis. The study focuses on two dimensions. First, regarding state authority, the post-reform SOE structure—comprising the State-Owned Enterprises Board (BP BUMN), BPI Danantara, and SOE Boards of Directors—corresponds to the doctrines of wilāyah ‘āmmah and wilāyah khāṣṣah, which justify delegated authority while maintaining accountability to the state. Second, regarding public interest, the principle taṣarruf al-imām manūṭun bi al-maṣlaḥah establishes public welfare as a condition of policy legitimacy. Drawing on al-Gazālī’s classification of maṣlaḥah mursalah, the analysis shows that efficiency gains at the taḥsīniyyāt level cannot justify weakening state control over interests categorized as ḍarūriyyāt. The study concludes that SOE governance must satisfy both constitutional and sharia-based legitimacy by prioritizing the collective public interest. Abstrak Pembentukan BPI Danantara sebagai superholding BUMN Indonesia telah memperbarui perdebatan mengenai keseimbangan antara kontrol negara dan logika pasar dalam pengelolaan aset publik strategis. Artikel ini mengkaji landasan normatif tata kelola BUMN melalui kerangka siyāsah shar'iyyah dengan pendekatan normatif-konseptual yang bertumpu pada literatur fikih klasik dan kontemporer serta analisis konstitusional. Kajian ini berfokus pada dua dimensi. Pertama, terkait kewenangan negara, struktur BUMN pascareformasi yang terdiri atas BP BUMN, BPI Danantara, dan Direksi BUMN sesuai dengan doktrin wilāyah ‘āmmah dan wilāyah khāṣṣah, yang memberikan dasar normatif bagi pendelegasian kewenangan dengan tetap menjaga akuntabilitas kepada negara. Kedua, terkait kepentingan publik, prinsip taṣarruf al-imām manūṭun bi al-maṣlaḥah menempatkan kemaslahatan publik sebagai dasar legitimasi kebijakan. Berdasarkan klasifikasi maṣlaḥah mursalah menurut al-Gazālī, analisis menunjukkan bahwa efisiensi pada tingkat taḥsīniyyāt tidak dapat dijadikan alasan untuk mengurangi kontrol negara atas kepentingan yang termasuk dalam kategori ḍarūriyyāt. Studi ini menyimpulkan bahwa tata kelola BUMN harus memenuhi legitimasi konstitusional sekaligus legitimasi normatif berbasis Syariah dengan tetap memprioritaskan kepentingan publik secara kolektif.